Enhancing Teaching Effectiveness to Foster Student Academic Motivation and Student Engagement in the EFL Classroom through Organization Development Interventions: An Action Research of Zhejiang Yuexiu University of Foreign Languages in China - Feng, Xiaolong; Kim, Seongdok (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
The issue of student engagement is crucial in that it is not only conductive to students’ academic development, but also influences their everyday experiences, both socially and physiologically. So far, there is a dearth of empirical research on implementing ODI to effectively foster student engagement in Chinese EFL classroom. Thus, a systematic inquiry through action research is considered necessary and imperative. This current research focused on enhancement of student academic motivation by implementing ODI in order to foster student engagement in the EFL classroom. The sample was 82 freshmen from two parallel classes. The experimental group was exposed to organization development interventions, including appreciative inquiry, goal setting, team building, differentiated instruction, whereas the comparison group received no intervention. Mixed research methods were adopted to collect and analyze the data. The paired-samples t test showed that there was statistically significant difference in student academic motivation and engagement for the experimental group between pre-ODI and post-ODI while there was no statistically significant difference for the control group. The Pearson’s Correlation Coefficient showed that there was a very strong positive relationship between academic motivation and student engagement. The qualitative analysis of students’ reflection reports and classroom observation feedback by three instructors justified how the ODIs employed in this research enhanced student academic motivation and student engagement. Based on the findings, critical recommendations for further research were discussed.